ANALISIS PERAN MANAJER DALAM MENGELOLA USAHA PADA UD. METE MUBARAQ - Younita, Vivi; Samdin, Samdin; Hastuti, Hastuti; Wati, Enny; Mokodompit, Eliyanti Agus; Sumarniwati, Putu (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2024)
The research aims to determine the role of managers at UD. Mete Mubataq. The informants in this research were 5 people divided into 1 owner, 1 manager, 2 marketing employees and 1 production employee. The sampling technique uses a Purposive Sampling technique where the researcher selects informants who have special characteristics so that they represent the required sample. The data collection method uses interviews. Researchers qualitative analysis, namely data reduction, dan presentation and drawing conclusasions. The results of this research show that the manager’s role as an interpersonal role does exits where work relationship such as manager production employees are given the task of producing cashew nuts and manager marketing employees are given the task or job of seeing or monitoring cashew stock that is decision maker information ready to be marketed. Information transfer role and decision-making role where managers provide information to employees to produce cashew nuts at a certain time and make decisions about how many cashews be produced at that time.